2022
DOI: 10.48550/arxiv.2203.07629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snowmass White Paper: Cosmology at the Theory Frontier

Abstract: The precision cosmological model describing the origin and expansion history of the universe, with observed structure seeded at the inflationary cosmic horizon, demands completion in the ultraviolet and in the infrared. The dynamics of the cosmic horizon also suggests an associated entropy, again requiring a microphysical theory. Recent years have seen enormous progress in understanding the structure of de Sitter space and inflation in string theory, and of cosmological observables captured by quantum field th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 297 publications
(431 reference statements)
0
15
0
Order By: Relevance
“…Others, involving non-perturbative effects, are still harder to understand in detail. Models of inflation and dark energy are discussed at greater length in §3 (on quantum gravity and cosmology) here, and in the white paper [8]. They require a level of theoretical control of effective po-tentials which remains just at the forefront of present technology.…”
Section: String Theory and Particle Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others, involving non-perturbative effects, are still harder to understand in detail. Models of inflation and dark energy are discussed at greater length in §3 (on quantum gravity and cosmology) here, and in the white paper [8]. They require a level of theoretical control of effective po-tentials which remains just at the forefront of present technology.…”
Section: String Theory and Particle Physicsmentioning
confidence: 99%
“…In this section we summarize the conclusions of the white paper [8], where an extensive list of references can be found.…”
Section: String Theory and Cosmologymentioning
confidence: 99%
“…This includes the inflationary and other early phases in the evolution of the Universe that could have generated a stochastic GW background (SGWB). (For synergy, see Snowmass white papers on inflation [3] and high energy physics model-building of the early Universe [4,5].) Later, Section 5 is dedicated to the open problem of dark matter.…”
Section: Introductionmentioning
confidence: 99%
“…in [47,48,49,50,51,52,53,54,55,56,57]. These references only scratch the surface, see the Snowmass whitepaper [58], for a review of the role of fundamental theory in cosmology, and [59] more specifically for a summary of effective field theories.…”
mentioning
confidence: 99%
“…Detailed reviews of EFT for other systems that include gravity can be found in the references, e.g. [58,59].…”
mentioning
confidence: 99%